AN INNOVATIVE APPROACH FOR ESTIMATION AND EVALUATION OF SPATIALLY DISTREIBUTED HYDROLOGICAL PARAMETERS WITH TEMPORAL RESOLUTION OF LAND USE-LAND COVER CLASSES USING REMOTE SENSING & GIS BASED ‘RINSPE’ MODEL - Kamuju, Narasayya. (IJRDO-Journal of Applied Science, 2016)
The estimation of Hydrological parameters of a catchment is an important aspect in engineering planning, environmental impact assessment, flood forecasting and water balance calculations. There have been efforts to estimate, analysis and evaluate the Hydrological parameters to make stable water use and other Hydrological problems to solve. This study focuses on the rainfall-runoff and infiltration estimation and evaluation of results by considering temporal resolution of Land use-Land cover classes using’Runoff-Infiltartion and nonPoint Source Pollution Estimation’ (RINSPE) model. To proceed this study through the ArcView selecting study area and collecting data, basically, are needed. This study chosen karha basin which is a sub-basin of Bhima basin and gathered various raster and feature class data. These collected data were used in preprocessing in the ArcGIS 9.3 for computing Hydrologic parameters. As input data for the rainfall-runoff model, this study selected the total 8 number of gauge stations. To reflect spatial rainfall characteristics of precipitation data of specific hydrologic events IDW method was used. Finally, RINSPE Model run in which SCS-CN method adopted for calculating runoff. The model run in two differ scenarios by considering temporal resolution of 10 years (2004-2013) for land use-land cover maps. The estimated runoff depths and infiltration were 268.63 mm, 281.02 mm and 315.65 mm, 316.88 mm from two differ years of 2004-05 and 2013-14 Land Use-Land Cover maps